Variations of Lower Limb Exercises to Increase Explosive Leg Power in Soccer - Alben, Ary Suud Cahyo; Mardius, Ali; Armen, Meiriani; Kumar, Alfiqroam; Ndaysenga, Japhet; Rahmalia, Apriyanti (Indonesian Journal of Sport Management, 2023)
Previous studies have found much of the effect of exercise on increasing the explosive power of leg muscles. However, research investigating variations in lower extremity muscle training forms to increase the explosive power of soccer players' leg muscles still needs to be completed. Therefore, references are needed to provide a fuller understanding and more effective solutions in designing training programs to increase the explosive power of leg muscles in soccer players. This study aimed to investigate the effect of various forms of lower extremity muscle training on increasing the explosive power of the leg muscles in soccer players. This study aims to provide a complete understanding of the types of exercises that are most effective in increasing the explosive power of the leg muscles, as well as to provide more effective solutions in the design of specific training programs for soccer players. Thus, this research should contribute to developing more optimal training methods and improving athletes' performance. This study uses the literature review method using a comprehensive strategy, such as searching for articles in the database of research journals. The databases used are Pubmed/MEDLINE, Scopus, Web of Science and Embase. The data used are the latest data from the last five years. Thus, recommendations of still very effective exercise variants can be recommended to trainers as a basis for creating training programs. Based on the analysis of research data, it has been found that strength training can increase the explosive power of the leg muscles. However, the study results showed that plyometric training was more effective than strength training in increasing explosive leg muscle power in soccer players. Therefore, a variation of plyometric exercises should be introduced to increase the explosive power of leg muscles in soccer players.